Chitosan-Activated Charcoal of Modified Corn Cobs as an Antibiotics Adsorbent - Gatut Ari Wardani; Clarisa Kartika Putri; Firman Gustaman; Taufik Hidayat; Estin Nofiyanti (Walisongo Journal of Chemistry, 2022)
Excessive use of tetracycline hydrochloride can cause water pollution. The concentration of tetracycline hydrochloride in an aqueous solution can be reduced by an adsorption method that utilizes activated charcoal as an adsorbent. This study aims to determine the effect of the addition of chitosan on the characteristics of activated charcoal, the effect of pH, adsorption kinetics, the adsorption isotherm, and the effect of sonication on adsorption ability. The method used in this research is the batch method combined with the sonication method. Based on this research, it is known that the use of ultrasonic waves (sonication) can streamline the adsorption process of tetracycline hydrochloride. The time required for the adsorption process is faster with greater adsorption capacity and efficiency. Tetracycline solution can be absorbed optimally at an acidic pH, which is pH 4. The adsorption process using the sonication method can increase the adsorption capacity from 2.092 mg.g-1 to 5.330 mg.g-1. The adsorption mechanism in both methods (batch and sonication) that occurs follows the kinetic equation of the two Ho pessaries. In contrast to adsorption kinetics, the adsorption isotherm for the batch method corresponds to the Langmuir adsorption isotherm equation (R2 = 0.950), while the use of the sonication method corresponds to the Freundlich isotherm equation (R2 = 0.859).  Thus, corn cob waste can be utilized by converting it into activated charcoal modified by chitosan as an adsorbent for antibiotic waste, especially tetracycline hydrochloride.